Procrastination and Aggression for Mental Disorders in Young People - Zvereva, M.V.; Enikolopov, S.N.; Oleichik, I. (Psihologičeskaâ nauka i obrazovanie, 2015)
The article presents analyze the phenomenon of procrastination and indirect manifestations of aggression in young people in normal health and mental disorders. Procrastination - a frequent phenomenon among young people, for this category the term “academic procrastination”; the high level of the various manifestations of aggression can also accompany adolescents in health and disease. The purpose of research is analysis of the relationship of procrastination and manifestations of aggression in health and mental disorders in adolescence. A complex of methods of psychological diagnosis, which included: questionnaire “Procrastination Assessment Scale for Students” (PASS, Solomon & Rothblum, 1984) Rosenzweig Frustration Test, Wagners Hand Test. We studied two samples of subjects 18-25 years: a control group of healthy young people (boys and girls) - 61 people, the experimental group - young people of both sexes who had mental disorders (schizophrenia, schizoaffective disorder, affective disorders – bipolar disorder, personality disorder) – 57. The results indicate the presence of the specific nature of components procrastination and indirect aggression manifestations of different levels at a young age for mental pathology. Работа посвящена анализу связи феномена прокрастинации и косвенных проявлений агрессии у молодых людей в норме и при психической патологии. Применялся комплекс методик психологической диагностики, в который входили: опросник «Шкала оценки прокрастинации PASS», тест фрустрационных реакций Розенцвейга, тест руки Вагнера. Исследованы две выборки испытуемых 18–25 лет: контрольная группа здоровых молодых людей (юношей и девушек) – 61 человек, экспериментальная группа – молодые люди обоего пола, имеющие психические расстройства (шизофрения, шизоаффективное расстройство, аффективная патология – биполярное расстройство, личностное расстройство) – 57 человек. Получены данные, указывающие на наличие нозоспецифического характера связи отдельных компонентов прокрастинации и проявлений косвенной агрессии разного уровня в молодом возрасте при психической патологии.